Ultrasonic characterisation of oil palm trunk infected by Ganoderma boninense disease - Mamat, Mohd Khairul Najmie (2011)
The ultrasonic characteristics for oil palm trunk which have been infected by Ganoderma boninense disease has been studied by using the ultrasonic commercial equipment at frequency 54 kHz. Among the physical characteristics that identifiable in oil palm tree that infected by Ganoderma boninense disease was by appearance a mature Ganoderma basidiocarp at the stem, lower fronds of an oil palm tree were dead and fractured. An oil palm tree of 30 years old has been used in this study. The measurement method used in this study was direct transmission method. The study of ultrasonic properties of oil palm trunk was infected with Ganoderma boninense disease were made in two stages; where in the first stage, measurement are made at standing oil palm tree and in the second stage; measurement was done in the cut trunk of stem centre to blocks size measuring 5 × 10 × 10 cm3. The number of samples used is 27 and consist of 3 sections namely: inner zone, central zone and peripheral zone. Results for standing oil palm tree showed that the ultrasonic velocity in the infected with Ganoderma boninense disease sample is between 350 – 600 ms-1 while healthy trunk the velocity was exceeding 700 ms-1. Measurement on the sample cut found that the trunk density of the sample infected decreased as much as 50% of the healthy stem. Percentage of moisture contents the infected areas also higher than the healthy areas. This affects the ultrasonic velocity through radial direction, tangential direction, and longitudinal direction for infected by Ganoderma boninense disease area which was consistently lower than healthy stem area. For the 10 cm thickness samples, the ultrasonic velocity for all transit directions was in the range of 260 – 750 ms-1 for the infected sample whereas for healthy samples was in the range of 460 – 900 ms-1. While, result of elasticity constant for the infected sample was between 0.2 – 8.5 (108 Nm-2) for all directions while the healthy area which was between 1.3 – 32.1 (108 Nm-2)for all directions. These results are very useful for the detection and identification of the location which has been affected by the disease.